FI’IL MUDHORI’ MANSHUB DALAM BUKU “RIYADHUS SHALIHIN” JILID 1 (Lisanul Arab: Journal of Arabic Learning and Teaching, 2012)
The term comes from the Greek Syntax, the sun which means 'with' and tattein which means 'place'. Etymologically, syntax means putting together words into a group of words or sentences. The ficil Mudhori 'could manshub as amyl nashob conceded. Amil nashob there is أن 10, لن, إذن, كي, لام كي, لام الجحود, حتى, فاء السببية, واو معية, and أو. The design of this research study or library research is often referred to as the research literature. Data analysis includes descriptive inductive analysis techniques. The results showed that the factors that led to ficil Mudhori 'be manshub in the book "Righteous Riyadhus" ie أن vol 1 no 163, there لن 14, لام كي No 8, No 2 لام الجحود, حتى there are 53, and there فاء سببية 19. While standing ficil Mudhori 'manshub in the book "Righteous Riyadhus" vol 1 no 8 خبر إن ie, there مستثنى 7, مفعول به no 110, there معطوف 66, معطوف عليه No 1, No 8 مجرور, there منصوب 12, مضاف إليه No 9, No 2 خبر كان, خبر No 6, No 1 خبر عسى, خبر أن no one, no one نعت جملة, مقل قول no 2, no 3 مبتداء مؤخر, there جواب 15, بدل No 4, No 1 فاعل , إسم إن No 1, No 1 إسم كان. And classification ficil Mudhori 'manshub in the book "Righteous Riyadhus" vol 1 by existing subject mufrod 219 pieces, while the classification ficil Mudhori' manshub in the book "Righteous Riyadhus" vol 1 by a plural subject, there are 34 pieces.